The innocents abroad ; Roughing it - Twain, Mark, 1835-1910 (Library of America, 1984)
Contains "The innocents abroad, a travel guide and stinging satire of his fellow American travelers," and "Roughing it, the old Western frontier adventures of Mark Twain."